2012
DOI: 10.1177/1028315311435418
|View full text |Cite
|
Sign up to set email alerts
|

International Student Security and English Language Proficiency

Abstract: International student security" refers to the international student's maintenance of a stable capacity for self-determining human agency. The article focuses on the role of English-language proficiency in the security of students from English as Foreign Language countries, drawing on evidence from a program of semistructured interviews with 200 international students. The interviews show that language proficiency is a pervasive factor in the human security of the international students in all domains inside an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
113
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(119 citation statements)
references
References 32 publications
6
113
0
Order By: Relevance
“…The perception of having limited communication skills hampers positive socialisation. Non-citizen students in English-language countries (Sawir, Marginson, Forbes-Mewett, Nyland & Ramia, 2012) who are unable to communicate in English feel they lack human security. Without the feeling of security, international students will avoid participation in activities involving non-Western individuals and confine their socialisation within groups of co-nationals.…”
Section: Linguistic Quadrantmentioning
confidence: 99%
“…The perception of having limited communication skills hampers positive socialisation. Non-citizen students in English-language countries (Sawir, Marginson, Forbes-Mewett, Nyland & Ramia, 2012) who are unable to communicate in English feel they lack human security. Without the feeling of security, international students will avoid participation in activities involving non-Western individuals and confine their socialisation within groups of co-nationals.…”
Section: Linguistic Quadrantmentioning
confidence: 99%
“…Researchers have identified language issues as a major concern for Asian and other international students (Counsell, 2011;Sawir, Marginson, Forbes-Mewett, Nyland, & Ramia, 2012;Zhai, 2002). However, not all international students have the same issues and regionally-specific information can help target programs for individuals and groups most affected by language issues.…”
Section: Cultural Concernsmentioning
confidence: 99%
“…In fact, Volet (1999, p. 628) points out that "The negative picture of Asian learners in Australian universities contrasts sharply with evidence from university statistics, that when English language proficiency is not an issue, Asian undergraduate students tend to perform better in their academic study than local students". Sawir, Marginson, Forbes-Mewett, Nyland, and Ramia (2012) investigated the role of English language proficiency in 200 English as a Foreign Language (EFL) students' communicative capacity both inside and outside the education setting (nine Australian universities) using semi-structured interviews. This study found that proficiency enables EFL students to move beyond passivity.…”
Section: L2 Students Of Asian Background In the Australian Learning Amentioning
confidence: 99%
“…The most fundamental issue that causes these challenges is low level of English language proficiency. For example, in a study (Sawir et al, 2012) on 200 international students 86% of whom were L2 students of Asian background, it was revealed that a number of academic difficulties were triggered by lack of English proficiency.…”
Section: L2 Students Of Asian Background In the Australian Learning Amentioning
confidence: 99%